Video Pijat Bayi sebagai Media Peningkatan Keterampilan Ibu dalam Merangsang Perkembangan Motorik Bayi - Taamu Taamu; Muslimin L; Desi Melina Saadi (Health Information : Jurnal Penelitian, 2019)
Baby massage has a very positive effect on the baby's growth and development process. This type of research is a Quasi experimental design with pretest-posttest control group design. The research location is Puskesmas Mokoau Kendari City. The population was infants aged 3 - 9 months. The sampling technique uses Quota and Accidental sampling techniques. The results showed that descriptively after being given a video massage, the majority of baby mothers, namely 66.67%, were skilled at infant massage. And after being given massage, the majority of babies, namely 93.33% of babies, had normal motor development. Inference, it is known that there is a significant difference in the massage skills of mothers with infants in the treatment group and the control group with p-value = 0.001 <? = 0.05 with the value of t-count = 6.162. Likewise, there was a significant difference in the motor development of infants in the treatment group given massage and the control group without massage with p-value = 0.031 <? = 0.05 with the value of t-count = 2.269. Thus it can be concluded that video infant massage is effective in improving massage skills of mother infants and giving infant massage is effective in improving motor development of infants aged 3 - 9 months.